ANALISIS KUALITAS PELAYANAN IZIN TRAYEK ANGKUTAN UMUM (Studi pada Badan Penanaman Modal dan Pelayanan Perizinan Terpadu Kabupaten Jepara) - Emil Rifqi; Turtiantoro .; Sulistyowati . (Journal of Politic and Government Studies, 2013)
Abstract BPMPPT of Jepara Regency is element of public service in the field of licensing of standing under and responsible to the Regents by a District Secretary. Licensing service that serviced by the other BPMPPT of Jepara Regency is public transport route permit service. In issue the route permit and supervision of public transport card, BPMPPT of Jepara Regency need to improve the quality service because most owners of public transport vehicles considered route permit service of process and control card takes a long time. So they are difficult to transport to the vehicle immediately. It would make them lose. And than they have the burden to be paid to the Bank, because most vehicle are purchased on credit. Purpose of this study is discover the underlying causes of less than optimal service in BPMPPT of Jepara Regency, and aware of the perceived impact of public transport owners as a result of less than optimal sevices. To learn the service factor blokers use Rusli theory about several factors that become obstacles in providing good service, among others : less responsive, less informative, less accessible, less coordination, bureaucratic, less willing to hear complain or recommendation from public, inefficiency. This study by descriptive analysis. Object study is public transport route permit service. The result showed that the length of permetting public transport route in BPMPPT of Jepara Regency occurs because BPMPPT chief factors as provider signature on the publik transit route permit card is frequent tasks outside the office. So file should be legalized on schedule to be delayed because of BPMPPT chief in outside office and longer settlement time. Key words : Public Transport Route Permit, Inhibiting Factors, Impact